ANALISIS PENGARUH PERBEDAAN LABA AKUNTANSI DAN LABA FISKAL TERHADAP PERSISTENSI LABA DAN ARUS KAS PADA KPRI “KARYA SEHAT” JOMBANG - Munawaroh Munawaroh (EKUITAS (Jurnal Ekonomi dan Keuangan), 2011)
Intention of this research is to know difference between accountancy profit and fiscal profit that is having an effect to persistension of profit and cash flow in one period to the fore and to know how difference impact between accountancy profit and fiscal profit to persistension of profit and cash flow.In writing of this research use approach of descriptive-quantitative at KPRI “Karya Sehat” Jombang. The method to collecting data that used is documentation and interview, while analysis of data use analysis examination of doubled regression.Pursuant to result of examination of data to doubled regression show result of that there are influence or regression between accountancy profit (X1) and fiscal profit (X2) by simultant to persistension of profit. While between accountancy profit (X1) and fiscal profit (X2) by simultant do not have an effect on to cash flow. Examination by parcial show result that there are no influence between variable of accountancy profit (X1) and fiscal profit (X2) to persistension of profit, while accountancy profit (X1) by parcial have an effect to cash flow (X2) but fiscal profit (X2) by parcial do not have an effect on to cash flow (X2). Pursuant to result of examination of data to test of SPSS, the data give information that have happened autocorrelasion at dependent variable persistension of profit, its intention that model of regression there is correlation between mistake of intruder at period of t with mistake of intruder at period of t-1 ( previous) and also happened multicolonieritasion with the meaning that model of regression have found there is existence of correlation between free variable ( independent ).